Synthesis and Characterization of Fluorinated β‐Ketoiminate Zinc Precursors and Their Utility in the AP‐MOCVD Growth of ZnO:F. Issue 26 (24th August 2015) - Cosham, Samuel D.; Kociok‐Köhn, Gabriele; Johnson, Andrew L.; Hamilton, Jeff A.; Hill, Michael S.; Molloy, Kieran C.; Castaing, Rémi
Abstract: A novel family of zinc bis(β‐ketoiminate) complexes2b –2h have been synthesized by reaction of the isolated free ligands1a –h with dimethylzinc. The isolated zinc complexes were characterized by elemental analysis, NMR spectroscopy, and in the case of2b –d and2f –h, the molecular structures of the complexes were determined by single‐crystal X‐ray diffraction which reveals the compounds to be pseudo ‐octahedral six‐coordinate, monomeric homoleptic complexes in the solid state. TG analysis showed complexes2b –f all to have residual masses at 400 °C of 10 % or less, well below the value for ZnO and thus indicative of volatility. Of these systems2b [Zn{MeC(O)CHC(NCH2 CH2 OMe)CF3 }2 ] has been investigated for its utility in the AP‐MOCVD growth of F‐doped ZnO (ZnO:F) in the absence of additional oxidant at 400 °C on glass and silicon substrates. Abstract : A family of novel bis(β‐ketoiminate) zinc precursors baring ether functionalized side arms, have been developed and evaluated for their use in the atmospheric pressure metal organic chemical vapor deposition growth of zinc oxide thin films. Fluorine doped ZnO thin films with a preferred orientation were grown on Si(100) and glass substrates.